Lift up Force on Concrete Blocks due to Tsunami - Azizah, Nurul; Triatmadja, Radianta; Kuswandi, Kuswandi (Civil and Environmental Engineering, Universitas Gadjah Mada, 2013)
Debris force on buildings due to tsunami may produce significant damage and create even further hazards and casualties. Debris such as a fraction of concrete column may be resulted from structures that were destroyed by tsunami. Concrete blocks pavement is also vulnerable as they be lifted up and drag away as debris by tsunami surge. The research deals with simulating the lift up force on concrete block under tsunami attack. The tsunami fronts were simulated using dam break system. The simulation was carried out at Hydraulics and Hydrology Laboratory Universitas Gadjah Mada Indonesia. The block was scaled down to match the capacity of the flume and other equipment. Finally a practical calculation was conducted to evaluate the condition of concrete block pavement in Parangtritis beach. It was found that a relatively small tsunami surge may lift the blocks up and drag them as debris.